A Green Revolution in Southern Niassa? A field study from a small farmer perspective about possibilities and obstacles for a Green Revolution. - Karin Gatu; Sofia Rodman (Växjö University, 2007)
The aim of this field study was to analyze, by taking into consideration the small farmers’ perspective, the possibilities and obstacles for an implementation of a Green Revolution in southern Niassa, Northern Mozambique. The authors also ask: in what sense are the findings in Asia, presented by Djurfeldt, relevant for thesituation in southern Niassa?
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura

Traditions and transitions : Islam and chiefship in Northern Mozambique, ca. 1850-1974 - Bonate, Liazzat J K (2007)
This thesis is based on the archival and fieldwork research, and sheds light on the area which has been little studied or reflected in scholarly literature: Islam in Northern Mozambique. Its particular focus is on African Muslim leadership in Northern Mozambique, which has historically incorporated Islamic authority and chiefship. The link between Islam and the chiefly clans existed since the eight century when Islam made inroads into the northern Mozambican coast and became associated with the Shirazi ruling elites. With the involvement of the region in the international slave trade during the nineteenth century, the Shirazi clans secured alliances with the most powerful mainland chiefs through conquest and kinship relations in order to access supplies of slaves from the mainland. This process was accompanied by a massive expansion of Islam from the coast into the hinterland. The alliances between the Shirazi at the coast and the chiefdoms further into the interior resulted in a network of paramount chiefs and their subordinates making up the bulk of Muslim slave-raiders, who established the limits between themselves (the Maca, Muslims and 'civilized') and those to be enslaved (the Makua and Lomwe, derogatory terms, meaning savagery, i.e., 'non-Muslims' and 'uncivilized')
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA